Secrets of question-based selling, 2nd edition how the most powerful tool in business can double your sales results - Freese, Thomas A. (Gildan Audio, 2020)
For nearly twenty years, The Secrets of Question Based Selling has been helping great salespeople like you deliver big results. Its commonsense approach has become a classic, must-have tool that demonstrates how asking the right questions at the right time accurately identifies your customer's needs.But consumer behavior and sales techniques change as rapidly as technology-and there are countless contradictory sales training programs promising results. Knowing where you should turn to for success can be confusing. Now fully revised and updated, The Secrets of Question Based Selling provides a step-by-step, easy-to-follow program that focuses specifically on sales effectiveness-identifying the strategies and techniques that will increase your probability of success.How you sell has become more important than the product. With this hands-on guide, you will learn to: penetrate more accounts; overcome customer skepticism; establish more credibility sooner; generate more return calls; motivate different types of buyers; develop more internal champions; close more sales ... faster; and much, much more.